2005
DOI: 10.1007/s10535-005-0104-8
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen nutrition of rice plants under salinity

Abstract: Two rice (Oryza sativa L.) cultivars, Koshihikari and Pokkali, were grown in solution culture at three concentrations of NaCl or Na 2 SO 4 [0 (S0), 50 (S1), and 100 (S2) mmol dm -3 ] and three N contents [0.7 (N1), 7 (N2) and 14 (N3) mmol dm -3 ]. Salinity significantly decreased dry matter of both cultivars. Pokkali had better growth than Koshihikari under both saline and non-saline conditions. Applications of N enhanced development of shoot dry mass under S0 and S1 treatments up to N2. Under S2, N applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 9 publications
6
20
0
Order By: Relevance
“…However, it has been reported that Cl − and Na + act in a combined fashion to give greater toxicity than when either ion is present in excess alone. [15] Similar findings on the comparisons between SO 4 2− and Cl − salinity were reported for the dry mass and root growth rate of rice, [16] maize, [17] and blueberry [18] at an equimolar concentration of Na. The greater yield reduction caused by NaCl salinity is probably associated with the higher rate of toxic Cl − ion accumulation.…”
Section: Discussionsupporting
confidence: 83%
“…However, it has been reported that Cl − and Na + act in a combined fashion to give greater toxicity than when either ion is present in excess alone. [15] Similar findings on the comparisons between SO 4 2− and Cl − salinity were reported for the dry mass and root growth rate of rice, [16] maize, [17] and blueberry [18] at an equimolar concentration of Na. The greater yield reduction caused by NaCl salinity is probably associated with the higher rate of toxic Cl − ion accumulation.…”
Section: Discussionsupporting
confidence: 83%
“…Rice is the most staple food for human (Peng, Laza, Visperas, Khush, & Virk, 2005), and it is more susceptible to the rhizosphere salinity than many other cereals (Joseph, Jini, & Sujatha, 2010). High Na + and Cl − concentration in saline soils have antagonistic effects on K, P, Zn, Fe, Ca, Mn and Mg ions (García et al., 2010; Ismail, 2009; Jung, Shin, & Schachtman, 2009), as well as nitrogen (N) uptake in rice crop (Abdelgadir, Oka, & Fujiyama, 2005). Consequently, seedling growth is inhibited (Gao, Chao, & Lin, 2007), number of tillers, panicles, and spikelets are reduced, and biomass and grain yield are decreased seriously (Abbas, Saqib, Akhtar, & Haq, 2015; Abdullah, Khan, & Flowers, 2001; Farshid & Hassan, 2012; Khatun & Flowers, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines exert their functions through complex interactions with metabolic networks, diverse-signaling pathways, and intricate hormonal cross-talks (Alcázar et al, 2010;Sequera-Mutiozabal et al, 2016). In addition to the salt composition (Abdelgadir et al, 2005), the N form might also affect the plant sensitivity to salinity (Speer and Kaiser 1994). At the whole-plant level, the effect of stress is usually perceived as a decrease in photosynthesis and growth, and it is associated with alterations in C and N metabolism (Garcıá-Mata and Lamattina, 2001).…”
Section: Differential Responses Of Genotypes To Salinity Levels and Nmentioning
confidence: 99%
“…It has been found that organic fertilization and mineral elements such as phosphorus and nitrogen can regulate plant drought stress responses by maintaining a higher relative water content, lower malondialdehyde, and promoting antioxidant enzyme activity such as superoxide dismutases and peroxidase (Li-Ping et al, 2006). N uptake and metabolism affect plant nutrient composition (Kováčik et al, 2012), contributing to nutrient balance and plant resistance to salt-stress (Mahmood and Kaiser 2003;Abdelgadir et al, 2005). Therefore, application of appropriate N fertilizer rate and source is a requirement of good agricultural practices in chamomile, which can affect not only quantitative traits but also its qualitative traits such as pharmaceutical properties and nutritional values (Andrzejewska and WoropajJanczak 2014).…”
Section: Differential Responses Of Genotypes To Salinity Levels and Nmentioning
confidence: 99%